Vocational English Lecturers’ Professional Identity: A Closer Look to the Six Domains - Cendra, Anastasia Nelladia; Sulindra, Eric (Soegijapranata Catholic University, 2024)
The growing research on teachers’ identity focused mostly on pre-service teachers, beginning teachers, and teachers at the secondary level. Research on teacher identity in the tertiary context has indeed been carried out, however, not much research has focused on the identity of English lecturers in vocational institutions, which arguably face more challenges compared to non-vocational counterparts. Teachers’ identity impacts the teaching process, in the way teachers see themselves, value their roles, and what their beliefs about teaching. These things significantly influence how they approach their work in the classroom. Aiming to fill in the gaps and add to the literature regarding the identity of vocational lecturers, this study seeks to answer three questions: (1) How do vocational English lecturers define their identities related to the six domains namely self-image, motivation, commitment, self-efficacy, task perception, job satisfaction, of teacher identity? (2) What are the things that cause the vocational English lecturer to define their identity, based on the six domains? (3) What are the advantages of knowing the teachers’ identity regarding the challenges that the vocational English lecturers face in their professional lives? The research used the purposive sampling method in qualitative research and was based on the saturation principle to determine the number of research participants. Using questionnaires and interviews with three participants as well as three-stage coding techniques and inductive analysis, this research found various positive identities within all six domains of teacher identity. These identities stem from both personal and contextual factors. Despite these promising findings, vocational English lecturers encounter certain challenges, notably with students who often have limited academic abilities, resulting in feelings of inadequacy, and a lack of enthusiasm for the English learning process.